Postglacial sea-level rise and sedimentar response in the Guadiana Estuary, Portugal/Spain border - Boski, T. (2013)
The study of sedimentological features, foraminifera and molluscan fauna in samples recovered from four rotary boreholes permitted, after 14C dating, the first assessment of the post-glacial transgression in Guadiana River Estuary. The Holocene sequence is underlain by coarse sediments from delta fan enclosing continental swamp deposits dated 16980 year BP. The Holocene sedimentary sequence was deposited either directly on this delta fan gravels or on top of fluvial sands deposited probably between 11000 and 10000 yr BP. An accelerated phase of the estuary infilling by clayey sediments containing the saltmarsh foraminifer Trochammina, began ca. 9800 year BP, when sea level was about 39 m below present. Between 7500 and 7000 year BP, the central part of the estuary started to accommodate coarser sediments, partially introduced from the continental shelf. The first phase of Holocene sea-level rise at a rate of 0.85 m/century terminated ca. 6500 year BP. Since then, lagoonal sediments in the vicinity of the estuary have been enclosed behind sand spits and predominantly sandy sedimentation was initiated within the estuary. After a second phase of slower rise at the rate of 0.3 m/century, which lasted until ca. 5000 year BP, the sea approached the present level.